Anisotropy-based inclination correction for the Moenave Formation and Wingate Sandstone: implications for Colorado Plateau rotation - McCall, Andrea M.; Kodama, Kenneth P. (Frontiers in Earth Science, 2014)
The ~ 201 Ma paleopole for North America at the Triassic-Jurassic boundary is observed in two widely different locations; one paleopole is determined from the Mesozoic rift basins in eastern North America and the other from the Colorado Plateau in the southwestern United States. A large discrepancy in paleopole positions from these two localities has been attributed to large amounts of clockwise vertical axis rotation of the Colorado Plateau (>10º) combined with inclination shallowing of the paleomagnetism. The sedimentary inclinations of the eastern North American basins have been corrected for shallowing, but the Colorado Plateau inclinations have not. Simple vertical axis rotation of the Colorado Plateau is not enough to bring the two paleopoles into agreement. This study of the Moenave and Wingate Formations was conducted to correct Colorado Plateau inclinations using their high field isothermal remanent anisotropy. The Moenave Formation and laterally equivalent Wingate Sandstone, which span the Triassic-Jurassic boundary, were sampled in southern Utah and northern Arizona. Thermal demagnetization isolated a characteristic remanence carried by hematite from 20 sites. High field (5 T) isothermal remanent anisotropy indicated shallowing of the characteristic remanence with an average flattening factor of f=0.69. An inclination-corrected paleopole for the Moenave and Wingate Formations is located at 62.5˚N 69.9˚E (α95=5.5˚) and is shifted northward by 2.9˚ with respect to the uncorrected paleopole. When the inclination corrected paleopole is rotated counterclockwise 9.7º about an Euler pole local to the Colorado Plateau, it is statistically indistinguishable from the inclination-corrected paleopole from the eastern North American rift basins. Rotation of the uncorrected paleopole does not bring it into statistical agreement with rift basin paleopole, therefore an inclination shallowing correction is necessary to support rotation of the Colorado Plateau and bring